2022
DOI: 10.3892/ijmm.2022.5162
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of circular RNA‑ZYG11B exerts a neuroprotective effect against retinal neurodegeneration

Abstract: Ischemic retinal diseases are the major cause of vision impairment worldwide. Currently, there are no available treatments for ischemia-induced retinal neurodegeneration. Circular RNAs (circRNAs) have emerged as important regulators of several biological processes and human diseases. The present study investigated the role of circRNA-ZYG11B (circ-ZYG11B; hsa_circ_0003739) in retinal neurodegeneration. Reverse transcription quantitative polymerase chain reaction (RT-qPCR) demonstrated that circZYG11B expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…cZRANB1 expression is significantly up-regulated during retinal neurodegeneration. Targeting cZRANB1 is an effective strategy for treating retinal neurodegeneration [ 2 , 11 , 12 ]. In this study, we reveal that silencing of cGlra2 can alleviate RGC apoptosis, decrease reactive gliosis, and reduce retinal cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…cZRANB1 expression is significantly up-regulated during retinal neurodegeneration. Targeting cZRANB1 is an effective strategy for treating retinal neurodegeneration [ 2 , 11 , 12 ]. In this study, we reveal that silencing of cGlra2 can alleviate RGC apoptosis, decrease reactive gliosis, and reduce retinal cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…We thus speculated that circRNAs also played critical roles in the process of retinal neurodegeneration. Previous studies have revealed that silencing of circZYG11B, circZNF609, or circZRANB1 plays a neuroprotective role in retinal neurodegeneration [ 11 , 12 ]. A study has been conducted to identify glaucoma-related cicRNAs in a rat glaucomatous model [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The sponging of miRNAs by circRNAs in most disorders highlights their potential as therapy candidates or biomarkers. For example, silencing circZYG11B could suppress I/R-induced RGC injury and attenuate I/R-induced retinal reactive gliosis through circZYG11B/microRNA-620/PTEN signaling; thus, circZYG11B might be a candidate for the identification and therapy of retinal ischemic diseases [135]. Chen et al [136] revealed that circHipk2 and circTulp4 can serve as sponges of miR-124-3p and miR-204-5p/miR-26a-5p, respectively, and the interruption of circTulp4 expression induced impaired retinal function.…”
Section: Circular Rnasmentioning
confidence: 99%
“…Several studies confirmed that RNFL and GCL thickness reduction precede functional deficits [8][9] . There is no proven treatment for retinal neurodegeneration but ongoing studies are aiming to provide evidence for treatment and neuroprotection [10][11] . There are many studies on the effects of MetS criteria such as HT, diabetes mellitus (DM), VO, and dyslipidemia on the retina [3,[12][13][14] .…”
Section: Introductionmentioning
confidence: 99%